Disturbances of peripheral vascular reaction to vasoactive substances and hypotensive therapy efficacy - G. I. Livshitz; A. A. Nikolaeva; K. Yu. Nikolaev (Российский кардиологический журнал, 2005)
The authors studied the influence of peripheral vascular reactivity dynamics on antihypertensive efficacy of beta-adrenoblockers, ACE inhibitors, and calcium antagonists, in hypertensive patients.